TEACHING AND LEARNING AMONG PRE- SCHOOL STUDENTS - Mahir, Isma Lebbe Mohamed; Nafla, Kalanthar Lebbe Fathima (International Journal of Psychosocial Rehabilitation, 2020)
From the time of their appearance, human beings have put in their full effort in the attempt to learn how to survive in this world. People then started living together in groups so that they could learn from each other and share a common pool of knowledge. Eventually, after a period of evolution, the behaviour of human beings came to be highly influenced and shaped by social, cultural, economic and environmental conditions. However, as these factors do not have the same effect on all persons they tend to mould them into distinct individuals, each with his/ her unique traits. The challenges faced, the tactics devised to handle those challenges and the previously learnt lessons from one’s own and other people’s experiences contribute to the personality development of every individual. This process starts from a very early age, even as a child starts to attend pre-school. At this stage, the child begins to understand its own wishes and desires and further, the direct immersion in that environment will help to develop its creative skills. While at pre-school, the child will start to think and understand about himself/ herself. It was in this regard the study was conducted, to learn about and analyse the learning and teaching activities taking place in the pre-schools that are not specifically institutionalized and supervised. This study was conducted in Digana in Kandy district in three selected pre-schools. A questionnaire, key-informant interviews and direct observation were used to collect primary data from teachers, students, and parents about the teaching and learning environment, processes and related activities. Relevant books, research articles, reliable web sources, newspaper articles and educational records were used as secondary data sources for this research. The primary data collected for this research were analysed using the descriptive analysis method and critical analysis method.